Harmony Search in Water Pump Switching Problem - Geem, Zong Woo (Advances in Natural Computation, 2005)
The purpose of this paper is to introduce a recently-developed nature-inspired algorithm, harmony search (HS), and to apply the algorithm to water pump switching problem. The HS algorithm is conceptualized using the musical improvisation process of searching for a better state of harmony. This paper describes a HS algorithm-based approach for the optimal switching problem in serial water pumping system. A standard example from the literature is presented to demonstrate the effectiveness of the proposed method, and the results are compared to genetic algorithm and branch & bound method. Computational results indicate that the HS approach becomes a good optimization model for solving water pump switching problem.